An investigation of security outcome convergence and the dynamics of their influencing factors in Africa. Issue 4 (2nd October 2021) - Saba, Charles Shaaba
ABSTRACT: This study explores the drivers of security outcome convergence for 51 African countries spanning the period from 2000 to 2018. Phillips and Sul convergence club and system generalised method of moments (SGMM) estimation techniques were applied. The main findings suggest security outcome convergence, and this implies that African countries are characterised by similar factors (economic, developmental, geographic and governance) which in turn determine an idiosyncratic course of their paths for security policies. The study further confirms that African countries in general appear to have gradually chosen at least to some extent similar paths for their security measures. It is asserted that the economic, developmental, geographic and governance policies pursued by African governments – and the ability of these governments to shape their policies – are likely to impact the process of security outcome convergence in Africa.